Preliminary Report of Rocket Observations of the Auroral Hiss - Tetsuo KAMADA (National Institute of Polar Research, 1975)
Two rockets with VLF receivers were launched from Syowa Station in Antarctica to study the electro-magnetic properties of auroral arcs. This paper is a preliminary report on the rocket observations. One payload was launched during relatively quiet auroral arc conditions. The other payload was launched while a 12 kHz VLF hiss recorder at a ground station showed fairly strong hiss, but no auroral arc was observed. In both cases, the electric field intensity in the VLF range was observed to increase at an altitude from 95 to 110km.